SEMANTIC FIELD RESEARCH IN COMPARATIVE PHRASEOLOGICAL UNITS OF ENGLISH AND UZBEK - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
In our article, we will determine the nature and location of comparative phraseology units in terms of semantics in English and Uzbek. A semantic classification of units was developed. It highlights the characters used in comparison units. It also sheds light on the mindset, everyday life, historical events, folklore, and beliefs of the people studied. Similarities and differences are outlined and discussed.